2002
DOI: 10.1021/es0157797
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Characterization of Microbial Communities That Reductively Dechlorinate TCE Based upon a Combination of Molecular Techniques

Abstract: An anaerobic microbial consortium (referred to as ANAS) that reductively dechlorinates trichloroethene (TCE) completely to ethene with the transient production of cisdichloroethene (cDCE) and vinyl chloride was enriched from contaminated soil obtained from Alameda Naval Air Station. ANAS uses lactate as its electron donor and has been functionally stable for over 2 years. Following a brief exposure to oxygen, a subculture (designated VCC) derived from ANAS could dechlorinate TCE only to vinyl chloride with lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
165
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 63 publications
(84 reference statements)
6
165
0
1
Order By: Relevance
“…The description of the community composition derived from metagenomic analysis is generally consistent with those of previous 16S clone library studies (Richardson et al, 2002;Lee et al, 2006) and the PhyloChip study presented here. Overall, data from the clone libraries and metagenome sequencing agreed on the most abundant bacterial taxa, which were also detected by the PhyloChip.…”
Section: Methanobacteriumsupporting
confidence: 85%
See 2 more Smart Citations
“…The description of the community composition derived from metagenomic analysis is generally consistent with those of previous 16S clone library studies (Richardson et al, 2002;Lee et al, 2006) and the PhyloChip study presented here. Overall, data from the clone libraries and metagenome sequencing agreed on the most abundant bacterial taxa, which were also detected by the PhyloChip.…”
Section: Methanobacteriumsupporting
confidence: 85%
“…ANAS enrichment culture and DNA sample preparation Culture conditions and maintenance procedures for ANAS have been described previously (Richardson et al, 2002). Briefly, 350 ml of culture was grown at 25-28 1C and 1.8 atm with a N 2 -CO 2 (90:10) headspace in a 1.5 l continuously stirred semi-batch reactor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extracts were visualized using electrophoresis on a 0.8% agarose gel. PCR targeting the 16S rRNA gene of all bacteria was performed as described by Dojka et al (2000) using primers 8f and 1492r (Richardson et al, 2002). Triplicate PCR products were pooled, purified by gel electrophoresis, and extracted using a MinElute Gel Extraction Kit (QIAGEN, Inc., Valencia, CA).…”
Section: Clone Library Constructionmentioning
confidence: 99%
“…(Richardson et al, 2002;Ritalahti and Löffler, 2004;Duhamel and Edwards, 2006;Lee et al, 2006), which are able to ferment organic substrates into hydrogen and acetate. Studies of a previously described dechlorinating microbial community, ANAS, showed that it was dominated by three bacterial groups: Dehalococcoides, Desulfovibrio and Clostridium, with the hydrogenotrophic methanogen Methanobacterium congolense (MC) as the dominant archaeal species (Richardson et al, 2002). Previous studies have shown that Desulfovibrio vulgaris Hildenborough (DVH) can transform lactate to acetate and H 2 when grown syntrophically with a H 2 -utilizing methanogen (McInerney and Bryant, 1981;Schink, 1997).…”
Section: Introductionmentioning
confidence: 99%